Multiband superconductivity in strongly hybridized 1T'-WTe₂/NbSe₂ heterostructures - Tao, Wei (2022)
The interplay of topology and superconductivity has become a subject of intense research in condensed matter physics for the pursuit of topologically non-trivial forms of superconducting pairing. An intrinsically normal-conducting material can inherit superconductivity via electrical contact to a parent superconductor via the proximity effect, usually understood as Andreev reflection at the interface between the distinct electronic structures of two separate conductors. However, at high interface transparency, strong coupling inevitably leads to changes in the band structure, locally, owing to hybridization of electronic states. Here, we investigate such strongly proximity-coupled heterostructures of monolayer 1T'-WTe$_2$, grown on NbSe$_2$ by van-der-Waals epitaxy. The superconducting local density of states (LDOS), resolved in scanning tunneling spectroscopy down to 500~mK, reflects a hybrid electronic structure, well-described by a multi-band framework based on the McMillan equations which captures the multi-band superconductivity inherent to the NbSe$_2$ substrate and that induced by proximity in WTe$_2$, self-consistently. Our material-specific tight-binding model captures the hybridized heterostructure quantitatively, and confirms that strong inter-layer hopping gives rise to a semi-metallic density of states in the 2D WTe$_2$ bulk, even for nominally band-insulating crystals. The model further accurately predicts the measured order parameter $Δ \simeq 0.6$~meV induced in the WTe$_2$ monolayer bulk, stable beyond a 2~T magnetic field. We believe that our detailed multi-band analysis of the hybrid electronic structure provides a useful tool for sensitive spatial mapping of induced order parameters in proximitized atomically thin topological materials.